PEMBUATAN TELUR ASIN AYAM RAS DENGAN PEMERAMAN LUMPUR PANTAI DAN UJI CITARASA PUTIH TELUR ASINNYA - Tenni Damayanti Indriastuti; Yorinda Buyang; Dirwan Muchlis (AGRICOLA, 2013)
The objective of the experiment was to know the effect ofmiddy deposit of ashorefor salt egg agent on albumen flavor layer chicken egg. The experimental design used was salt content and flavor for salty egg productwith the result that middy deposit for sains and technology.The results of Spider diagram indicated for salt conten in middy deposit of very low and odour to salt egg product.The conclusion of this research was that the middy deposit of applicable to agent  but have to increasingly salt andnoodour middy deposit.